Updates to the antitumor mechanism of oncolytic virus - Bai, Yang (Thorac Cancer, 2019)
Oncolytic viruses (OVs) are promising new therapeutic agents in the field of malignant tumor treatment. OVs can achieve the goal of targeted therapy by selectively killing tumor cells and inducing specific antitumor immunity. The key roles of OVs are tumor targeting and tumor killing mechanisms. Recently, molecular biotechnology has been used to optimize the transformation of wild virus strains in order to ensure a stronger oncolytic effect and lower adverse reactions, to enable testing in clinical trials as an antitumor drug. The main purpose of this review is to provide a description of oncolytic mechanisms, clinical studies, combination therapies, current challenges, and future prospects of OVs.